كتب تعليم اللغة العربية في ماليزيا ودول جنوب شرق آسيا: من رهانات بناء قدرات التأليف الوطنية إلى رهان الجودة التربوية - Chik, Abdul Rahman (2015)
An analysis study on Arabic language textbooks used in Malaysia and Southeast Asian countries. Raising the bar of excellence in authorship towards a Total Quality Management in Arabic language Education.